2022
DOI: 10.5603/fhc.a2022.0005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 inhibits apoptosis of rat gastric smooth muscle cells under high glucose condition via adenosine monophosphate-activated protein kinase (AMPK) pathway

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Histochemica et Cytobiologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These findings suggested that IGF1 is the vital activator of RORα in early bone repair. It is well known that adenosine monophosphate‐activated protein kinase (AMPK) and mitogen‐activated protein kinase (MAPK) pathways are the classical downstream intracellular signal pathways of IGF1, 24 , 25 so we tested whether IGF1 regulated the expression of RORα by these two pathways. AMPK activator AICAR promoted phosphorylation of AMPK and RORα expression in THP‐1 cells (Figure 4I,J ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that IGF1 is the vital activator of RORα in early bone repair. It is well known that adenosine monophosphate‐activated protein kinase (AMPK) and mitogen‐activated protein kinase (MAPK) pathways are the classical downstream intracellular signal pathways of IGF1, 24 , 25 so we tested whether IGF1 regulated the expression of RORα by these two pathways. AMPK activator AICAR promoted phosphorylation of AMPK and RORα expression in THP‐1 cells (Figure 4I,J ).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that adenosine monophosphate-activated protein kinase (AMPK) and mitogen-activated protein kinase (MAPK) pathways are the classical downstream intracellular signal pathways of IGF1, 24,25…”
Section: Insufficient Igf1-ampk Signalling Of Dm Rats Blocks Upregula...mentioning
confidence: 99%
“…Available data on the role of AMPK in the regulation of apoptosis are controversial. While some reports suggest AMPK-dependent stimulation of apoptosis [ 39 , 40 , 41 ], several studies demonstrate an anti-apoptotic role of AMPK [ 22 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%